The Impact of the European Carbon Market on Firm Productivity: Evidence from Italian Manufacturing Firms - Filippo Maria D'Arcangelo; Giulia Pavan; Sara Calligaris (Fondazione Eni Enrico Mattei (FEEM), 2022)
The European Union Emissions Trading System has raised concerns about possible detrimental effects on firms production through an increase in polluting costs, unless firms change inputs or increase the efficiency in the way they produce. We provide evidence of the causal impact of this policy on firms' input choices and on total factor productivity on Italian manufacturing firms. Our empirical strategy combines structural estimation of firms' production function and techniques for policy evaluation. Moreover, we argue that a commonly used strategy in this literature, consisting in using propensity score matching on the productivity obtained from estimating the production function, does not provide valid inference. We rely instead on an innovative structural approach. We find that the policy has a small negative effect on productivity that is heterogeneous across industries. We show that these findings are consistent with firms switching fuels in production, rather than undergoing a substantial process change.
Keywords: Q58; L23; L26; 330; Emission trading; EU ETS; Environmental Policy; Manufacturing; Productivity; Production Function